Engineering of Extracellular Matrix‐Like Biomaterials at Nano‐ and Macroscale toward Fabrication of Hierarchical Scaffolds for Bone Tissue Engineering. Issue 2 (29th November 2021) - Lemos, Rafael; Maia, F. Raquel; Reis, Rui L.; Oliveira, Joaquim M.
Abstract : The increasing rate of musculoskeletal pathologies has compelled the development of improved and novel treatment strategies in order to address unmet clinical needs. Tissue engineering approaches comprising the use of scaffolds for bone regeneration have been showing to be a promising alternative to conventional bone repair/substitution approaches. In particular, hierarchical scaffolds as methods of structural support and osteogenic differentiation promoters are among the most used tools in bone tissue engineering (BTE). In this reasoning, hierarchical scaffolds have sparked the field, striving toward mimicking the natural bone tissue in both, its complex 3D structure and composition. A recent and promising trend has been the merging of nanotechnology and tissue engineering concepts. As such the incorporation of nanoparticles and nanocomposites into micro‐ or macroscaffold systems can result in an improvement of scaffolds' biofunctionality at different levels. These tools are versatile in nature and can be used for multiple purposes such as drug delivery, thermal conductors, and mechanical reinforcement. Taking into consideration multidisciplinary approaches, several strategies have been pursued. The recent reports dealing with the approaches pursued in the hierarchical scaffolds production and enhancement, ranging from the nanoscale to the macroscale, are overviewed herein. Abstract : Hierarchical scaffolds have been sparked in the bone tissue engineering field, striving toward mimicking the natural bone. Furthermore, the merge of nanotechnology and tissue engineering has enabled the improvement of scaffolds' biofunctionality. The current materials of interest and top‐down approaches pursued by hierarchical scaffolds' production and enhancement, ranging from the nanoscale to the macroscale, are overviewed herein.